MORPHOLOGICAL CHARACTERISTICS OF RENAL STRUCTURES IN NEWBORNS IN THE NEONATAL PERIOD (International journal of medical sciences, 2026)
The aim of the study was to evaluate the morphological features of the renal structures of neonates who died in the neonatal period, taking into account the gestational age and the leading cause of death. A comprehensive macro- and microscopic analysis of renal tissue was conducted using morphometric methods. It was established that the kidneys of newborns are characterized by morphofunctional immaturity of the glomerular and tubular apparatus, pronounced variability in the degree of nephron differentiation, and high sensitivity to hypoxic-ischemic and infectious-toxic effects. In hypoxic conditions, glomerular collapse, capillary stasis, dystrophy and necrosis of the tubular epithelium, and interstitial edema were detected. In sepsis, signs of thrombovasculitis and diffuse inflammatory infiltration were noted. The obtained data are important for neonatology, pathological anatomy, and forensic practice.